I am really, really concentrating - Child, Lauren; Hill, Samantha; Tiger Aspect Productions (New York : Grosset & Dunlap, 2008)
Lola, who is small and very funny, prepares for Field Day with help from her older brother Charlie, and her friends Lotta and Marv, but while she finds that most of the games are difficult, she might do well in the egg-and-spoon race, if she practices her concentration.
"As seen on Playhouse Disney"--Cover.
2.2
K-3.
K-3
Keywords: Attention -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Attention -- Fiction; Brothers and sisters -- Fiction; Attention -- Fiction; Siblings -- Fiction